Sistem Pendukung Keputusan Pemilihan Induk Ikan Lele yang Berkualitas Untuk Meningkatkan Produksi Benih Ikan Lele Menggunakan Metode MOORA (Multi-Objective Optimization On The Basis Of Ratio Analysis) - Dwi Nanda Cahyo; Muhammad Zunaidi; Widiarti Widiarti (JURIKOM (Jurnal Riset Komputer), 2019)
The demand for national catfish seeds continues to increase. Therefore, catfish hatchery is a very prospective business for the future. The quality of the catfish parent in Indonesia which has greatly decreased makes the cultivation time longer and the quality of the seeds less good. To get good catfish seeds, researchers must look for quality catfish first. Before spawning, the mother catfish must feed a lot and also vitamins first in order to increase their production. In this case, the Decision Support System for Determining quality catfish is made using the MOORA (Multi-Objective Optimization Based on Analysis of Ratio) method, a method that will determine the choice to look for quality ones. Results Conclusions with this system indicate a system that determines predetermined criteria.